(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of cesarean sections indicated by failure of head descent at the National Hospital of Obstetrics and Gynecology. Subjects and methods: A study of 218 pregnant women who underwent cesarean sections due to failure of head descent in the first 6 months of 2024 at the National Hospital of Obstetrics and Gynecology. Results: Gestational age between 37 and under 40 weeks accounted for 64.2%, comprised of 59.6% primiparas and 4.6% multiparas. Gestational age between 40 and under 42 weeks accounted for 35.8%, comprised of 31.7% primiparas and 4.1% multiparas. Neonates weighing 3000 to under 3500 grams constituted the majority at 59.6% (primiparas 55%, multiparas 4.6%). In all 218 cases, the Apgar scores at the 1st and 5th minutes were > 7. The majority of patients underwent cesarean section within 60-90 minutes after full cervical dilation (93.1%). Most patients underwent surgery within < 6 hours of membrane rupture (64.2%), followed by 6-12 hours (21.1%), with only 14.7% exceeding 12 hours. Among the 218 cases, 16 patients experienced complications (7.3%): extension of the uterine incision (5.5%); placental site hemorrhage (0.9%); accidental ureteral suture (0.5%); and surgical site infection (0.5%). Conclusion: The majority of cases were operated on at an appropriate time, maximizing safety and minimizing the risk of adverse events and complications.